EFEKTIVITAS MODEL THINK TALK WRITE DAN THINK PAIR SHARE TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS 4 SD - Endah Murwatiningsih; Wahyudi Wahyudi; Yohana Setiawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2019)
The purpose of this research is to identify the difference between the effectiveness of TTW and TPS models towards the improvement of ability in on 4th grader elementary school students. This experiment is a pseudo-experimental research. The sample of this research are 27 students of SDN Lodoyong 02 and 23 students of SDN Lodoyong 03.The data analytic used is pre-requisite test which showing the result of both groups are distributed normally and not homogeneous. The test of Independent sample T-test acquired t-count > t-table is 2,344>2,011 and score signification 0,023<0,05 which showing that Ho is refused and Ha is accepted. N-gain scoring analysis shows a student improvement after applying TTW model approximately 0,391 meanwhile after applying TPS model approximately 0,33. From the result of n-gain scoring, the difference of the two models can be seen approximately 0,061. Based on the data analysis, it's concluded that there is a difference of effectiveness which is significant. The applying of ttw model has a level of effectiveness higher than tps model towards the ability of mathematical communication on 4th grader students of elementary school.